UNSATURATED COPOLYMER, ITS PRODUCTION, MODIFIED COPOLYMER AND UNSATURATED COPOLYMER COMPOSITION - MORIYA SATORU; MORI RYOJI; OTA SEIJI (1999)
PROBLEM TO BE SOLVED: To obtain the subject copolymer excellent in compatibility with other polar group-containing resin and capable of exhibiting excellent crosslinking efficiency and modification efficiency by copolymerizing a specific α-olefin with a cyclic olefin and a conjugated diene monomer. SOLUTION: This copolymer is obtained by copolymerizing (A) a 2-12C straight-chain or branched chain α-olefin with (B) a cyclic olefin, preferably having a structure of formula I [(n) is 0 or 1; (m) is 0 or positive integer; (q) is 0 or 1; R to R , R and R are each H, a halogen, a hydrocarbon group, etc.), or formula II [(p) and (q) are each 0 or positive integer; (m) and (n) are each 0, 1 or 2; R to R are each H, a halogen, an alkoxy, etc.), and (C) a conjugated diene monomer, preferably of formula III [R and R are H, a 1-8C alkyl or an aryl, with the proviso that at least one of R and R is H]. The copolymer has <=25 deg.C glass transition temperature (Tg) measured by differential scanning calorimeter.